Analiza i ocena pakietu legislacyjnego Komisji Europejskiej oraz stanowiska polskiego Ministerstwa Rolnictwa i Rozwoju Wsi dotyczących kształtu Wspólnej Polityki Rolnej Unii Europejskiej po 2013 roku - Walkowski, Maciej (Przegląd Politologiczny, 2018)
The Common Agricultural Policy of the European Union plays a particular role in the process of European integration and the implementation of numerous community goals that go beyond the traditional functions of agriculture, associated with the production of food, and concern the multifunctional development of rural territories. The CAP played the main role in enlarging the EU, by incorporating the twelve new states from Central and Eastern Europe by means of ensuring their smooth integration into the common market and facilitating the accelerated adaptation, modernization and restructurization of the agricultural and food sectors, as well as the non-agricultural fields of the socio-economic and cultural activation of rural populations. The EU’s agricultural and rural policy continues to undergo evolutionary transformation, and its shape in the new 2014–202 financial perspective is of vital and justified interest for Poland. The paper presents the latest proposals of the European Commission in this respect, presented on October 12, 2011, the Polish official negotiating position and the author’s assessments, opinions and predictions.